Constitutional and legal foundations of the institution of citizenship - Balgimbekova, G.U.; Yerzhanova, F.A (Bulletin of the Karaganda University “Law Series”, 2023)
In this article, based on the study and analysis of the current legislation of the Republic of Kazakhstan and foreign countries, scientific literature in the field of citizenship, current issues of legal regulation of the institution of citizenship are considered. The central place is given to the study of the Constitution of the Republic of Kazakhstan, the Law “On Citizenship of the Republic of Kazakhstan”, foreign experience of the constitutional and legal regulation of citizenship is considered. The article shows that the institution of citizenship is of fundamental importance for the development of the state and society, the formation of civil society. The authors note that one of the main problems of the theory and practice of constitutionalism is the development and ensuring of human rights and freedoms through the constitutional institution of citizenship. The issues of constitutional and legal regulation of citizenship in the legislation of the Republic of Kazakhstan and foreign countries have been studied. The authors present the main points of view on the issues of defining the concept of citizenship, identifying its essence and significance in the constitutional and legal construction. Conclusions are drawn, in particular, that the Constitution of the Republic of Kazakhstan as a whole corresponds to the world trends in the development of constitutional law, due to the general globalization and internationalization of law. As one of the directions for further improvement of the constitutional and legal legislation, a proposal was formulated to include in the constitutional and legal legislation a provision on the generally recognized principles and norms of international law on human rights